Design of complex coil geometries for magnetic particle imaging using additive manufacturing (Transactions on Additive Manufacturing Meets Medicine, 2024)
Field-generating coils are extensively used in different areas of medical imaging. They are employed not only in well-established clinical applications (magnetic resonance imaging (MRI)) but also in areas where preclinical research is ongoing (magnetic particle imaging (MPI), magnetoencephalography (MEG), magnetic induction tomography, and others). Depending on the application and technical requirements, it may be necessary to develop complex windings that follow the anatomy of the specific area of the human body. In this case, traditional manufacturing methods are too expensive or limited in their capabilities, while additive manufacturing grants the freedom to create almost any shape.  In this work, we demonstrate a prototype of an anatomically optimized coil set for MPI of the human brain, fabricated using additive manufacturing technologies. The coil set has a power efficiency advantage over previously demonstrated cylindrical shapes, which has the potential for implementation in portable tomographic devices.
Keywords: coils; magnetic particle imaging; tomography; electromagnetics; FDM; SLA; Magnetic field; Stroke